2001
DOI: 10.1016/s0008-6363(01)00391-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum depletion induces cell loss of rat cardiac fibroblasts and increased expression of extracellular matrix proteins in surviving cells

Abstract: Serum depletion led to cell death of isolated cardiac fibroblasts. Survival was associated with the increase in the expression of various ECM proteins. The transcription factor CREB was activated after serum removal. Inhibition of PKA improved the serum depletion induced decrease in the survival rate. The increase in collagen I, collagen III, MMP-2, TIMP-2, and colligin evoked by serum depletion was also diminished by PKA inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 45 publications
2
20
1
Order By: Relevance
“…The NE concentration and the induction time for apoptosis in these studies were similar to the findings in ours using CF. In a previous study, Leicht et al observed that serum withdrawal could lead to a 36% cell loss in CF due to necrosis [20]. However in our study, the significant increase in apoptotic cell percentage did not due to serum withdrawal but NE induction.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The NE concentration and the induction time for apoptosis in these studies were similar to the findings in ours using CF. In a previous study, Leicht et al observed that serum withdrawal could lead to a 36% cell loss in CF due to necrosis [20]. However in our study, the significant increase in apoptotic cell percentage did not due to serum withdrawal but NE induction.…”
Section: Discussioncontrasting
confidence: 80%
“…Conversely, there are situations where CF can undergo programmed cell death. Stimulants including angiotensin II modulated nitricoxide production [16], osmotic stress [18], osteopontindeficiency, interleukin-1β-induced nitric-oxide production [19] and serum-free condition [20] can induce apoptosis and necrosis in CF. It is important for the heart to maintain a balance population of myocytes and non-myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…First, because MMP-2 release even in controls gradually increased time-dependently, the culturing conditions may partly offset the difference in MMP-2 abundance between BNP-treated cell cultures and controls. Supporting this hypothesis, a study by Leicht et al 42 showed that serum depletion increased the MMP activity in rat CFs. Second, high concentrations of BNP were needed in this cell culture system to increase intracellular cGMP.…”
Section: Discussionmentioning
confidence: 85%
“…3 and 4). Transcriptional regulation of TIMPs is mediated by cytokines and phorbol esters (Leicht et al, 2001). Although we did not examine the details for effects of IR positive on MMPs and negative on TIMP-4, the changes seemed to be governed by ERK after EPO treatment (Figs.…”
Section: Discussionmentioning
confidence: 96%